Civil 'jurisdiction' of Syariah Court in Malaysia - should it be expressed or implied? : A reflection - Md Dahlan, Nuarrual Hilal; Kamaruddin, Abdul Rani (2005)
The jurisdiction of Syariah Courts to hear matters its own matters is generally provided and fallen under List II (State List) of the 9th Schedule to the Federal Constitution ('FC') and specifically provided in the respective states' enactments on the administration of Islamic Law enactments and for the Federal Territories, an act passed by Parliament However, there are certain matters that have been left by the legislatures to have them being specifically provided in the said provisions even though it involves the determination of Islamic Law as enshrined in List Il (State List) under the Ninth Schedule to the FC, In such situation, what is the position of Syariah Court? Could it determine the matters even though it had not been provided by the legislature?. This paper will highlight these issues through cases decided in courts in Malaysia.